Old Hickory's Nephew : The Political and Private Struggles of Andrew Jackson Donelson - Cheathem, Mark Renfred (Book collections on Project MUSE., 2007)
Though remembered largely by history as Andrew Jackson's nephew, Andrew Jackson Donelson was himself a significant figure in nineteenth-century America: a politician, planter, diplomat, newspaper editor, and vice-presidential candidate. His relationship with his uncle and mentor defined his life, as he struggled to find the political and personal success that he wanted and his uncle thought he deserved. In Old Hickory's Nephew, the first definitive biography of this enigmatic man, Mark R. Cheathem explores both Donelson's political contributions and his complex, tumultuous, and often-overlooke.